Neonatal Epilepsies and Seizure Evolution - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The evolution of epileptic syndromes in 75 children with EEG-confirmed epilepsies of neonatal onset was studied at Nagoya University, Japan.